Two Worlds Apart: A Comparative Analysis of the Effectiveness of Domestic Abuse Law and Policy in England and Wales and the Russian Federation. (October 2019) - Richardson, Kayliegh; Speed, Ana
In 2015, s 76 of the Serious Crime Act 2015 introduced the new criminal offence of 'controlling or coercive behaviour in an intimate or family relationship'. This is just one of many steps the UK government have taken in recent years to acknowledge the different forms of domestic abuse and power imbalances that can be present in intimate relationships. In contrast, in February 2017, the Russian government passed an amendment to the Russian Criminal Code to decriminalise some forms of assault, a step which many human rights activists have opposed. This article will compare the seemingly dichotomous approaches to domestic abuse adopted by England and Wales and Russia and will examine the effectiveness of both approaches in deterring domestic violence, providing adequate support for victims and meeting state obligations under international law. There has been extensive commentary on the approach to domestic abuse in England, the USA and Australia. In comparison, consideration of the approach in the Russian Federation is limited. This is in part due to the approach taken in Russia to dealing with domestic abuse as a private issue and the associated lack of available data. This article seeks to go behind closed doors to explore the Russian approach to tackling domestic abuse in a way that it has not previously been considered.